2020
DOI: 10.1002/mdc3.12968
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Determinants of Neuropsychiatric Symptoms in Late‐Stage Parkinsonism

Abstract: BackgroundBackground: Late-stage parkinsonism and Parkinson's disease (PD) are insufficiently studied population. Although neuropsychiatric symptoms (eg, psychosis, depression, anxiety, behavioral problems) are frequently present, their prevalence and clinical predictors remain unknown. Objective Objective: To determine the prevalence and predictors of neuropsychiatric symptoms in late-stage PD. Methods Methods: We conducted a multinational study of patients with PD with ≥7 years disease duration and either a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 66 publications
2
40
0
2
Order By: Relevance
“…The frequency we found was similar to the ones reported in few previous studies that reported on hallucinations/psychosis among LSPD patients. Indeed 41% (vs. 43.7% in our sample) of hallucinations have been reported in a large cohort of 623 LSPD patients in agreement with the NPI [7] or 56% (52.3% in our sample) of psychosis in a smallest cohort of 50 patients, in agreement with the MDS-UPDRS item 1.2 [7] . At the same time, comparison among those tests and the CDI have been not performed previously, particularly among LSPD patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The frequency we found was similar to the ones reported in few previous studies that reported on hallucinations/psychosis among LSPD patients. Indeed 41% (vs. 43.7% in our sample) of hallucinations have been reported in a large cohort of 623 LSPD patients in agreement with the NPI [7] or 56% (52.3% in our sample) of psychosis in a smallest cohort of 50 patients, in agreement with the MDS-UPDRS item 1.2 [7] . At the same time, comparison among those tests and the CDI have been not performed previously, particularly among LSPD patients.…”
Section: Discussionsupporting
confidence: 88%
“…For all these reasons, it is difficult to estimate the true prevalence of PDP. It is well established that PDP is more frequent with advancing disease [5] and a high frequency of psychosis and neuropsychiatric symptoms have recently been reported in a multicenter cohort of late-stage (LS) parkinsonism using the Neuropsychiatric Inventory (NPI) [7] . LSPD patients still represent “an orphan” population, whose clinical criteria have been recently proposed [8] , [9] but still poorly described due to the difficult for those patients to be included into clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, caregiver burden in PD is assessed by generic questionnaires. These tests do not explicitly evaluate all specific aspects of caregiver burden in PD, although the course of PD is different from other geriatric diseases, e.g., due to various motor and non-motor symptoms and long disease duration with progressive impairments in the activities of daily living [6,7]. The recently developed and validated Parkinson's disease caregiver burden questionnaire (PDCB) offers a special opportunity to study disease-specific aspects of caregiver burden in PD [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, this study showed that neuropsychiatric symptoms in total are very frequent. Hommel et al also reported that a high prevalence of neuropsychiatric symptoms (particularly apathy, depression, and anxiety) is the strongest predictor for more neuropsychiatric symptoms in late-stage PD [ 52 ]. Hence, screening for other psychiatric comorbidities, such as with the SEND-PD, is already crucial in the early stage of the disease [ 52 ].…”
Section: Discussionmentioning
confidence: 99%